2002
DOI: 10.1038/sj.onc.1205502
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase/MT-SP1 is required for postnatal survival, epidermal barrier function, hair follicle development, and thymic homeostasis

Abstract: Matriptase/MT-SP1 is a novel tumor-associated type II transmembrane serine protease that is highly expressed in the epidermis, thymic stroma, and other epithelia. A null mutation was introduced into the Matriptase/MT-SP1 gene of mice to determine the role of Matriptase/ MT-SP1 in epidermal development and neoplasia. Matriptase/MT-SP1-de®cient mice developed to term but uniformly died within 48 h of birth. All epidermal surfaces of newborn mice were grossly abnormal with a dry, red, shiny, and wrinkled appearan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
314
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(332 citation statements)
references
References 58 publications
10
314
1
7
Order By: Relevance
“…A proteolysis-independent role of HAI-1 in embryonic development has also been proposed (Tanaka et al, 2005), because HAI-1 is an integral transmembrane protein with a cytoplasmic tail domain that is potentially capable of transducing extracellular signals, and because hepatocyte growth factor activator, hepsin, and matriptase are all dispensable for mouse embryonic development (Wu et al, 1998;List et al, 2002;Itoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A proteolysis-independent role of HAI-1 in embryonic development has also been proposed (Tanaka et al, 2005), because HAI-1 is an integral transmembrane protein with a cytoplasmic tail domain that is potentially capable of transducing extracellular signals, and because hepatocyte growth factor activator, hepsin, and matriptase are all dispensable for mouse embryonic development (Wu et al, 1998;List et al, 2002;Itoh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gene targeting studies in mice have revealed an essential role of the protease in postnatal oral and epidermal barrier formation and hair follicle growth (List et al, 2002(List et al, , 2006. However, matriptasedeficient mice develop to term, and they display no obvious developmental abnormalities besides the skin and oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…6−8 Matriptase or MT-SP1 is a type II transmembrane serine protease (TTSP) that is mainly expressed in the epidermis, thymic stroma, and other epithelia. 9,10 The proteolytic activity of matriptase is controlled by hepatocyte growth factor activator inhibitor-1 (HAI-1). 9,10 Knockout mouse studies have revealed that matriptase plays a role in terminal differentiation of epidermis, hair follicle development, and thymic homeostasis.…”
mentioning
confidence: 99%
“…9,10 The proteolytic activity of matriptase is controlled by hepatocyte growth factor activator inhibitor-1 (HAI-1). 9,10 Knockout mouse studies have revealed that matriptase plays a role in terminal differentiation of epidermis, hair follicle development, and thymic homeostasis. 9 Relative ratio of matriptase to HAI-1 is reported to be higher in a range of epithelial tumors, in which active matriptase plays an important role in cellular invasion and metastasis.…”
mentioning
confidence: 99%
“…Indeed, mice lacking St14 (matriptase) or Prss8 (prostasin) genes showed a severe defect in epidermal barrier function and died from dehydration early in neonatal development. 36,37 In humans, amino acid substitutions in the highly conserved protease domain of matriptase result in reduction or loss of matriptase activity and cause autosomal recessive ichthyosis with hypotrichosis. 38 On the other hand, excess expression or activity of serine protease is associated with skin disorders.…”
Section: Discussionmentioning
confidence: 99%